49th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2011
DOI: 10.2514/6.2011-586
|View full text |Cite
|
Sign up to set email alerts
|

Detonation Initiation by a Gradient Mechanism in Propane-Oxygen and Propane-Air Mixtures

Abstract: An experimental study of detonation initiation by high-voltage nanosecond gas discharge has been performed in smooth detonation tubes. A gradient mechanism was used to initiate detonations in stoichiometric propane-oxygen mixtures with different nitrogen dilution and in propane-air mixtures. Initial pressures from 0.2 to 1 bar have been tested. Detonation was formed within 4 transverse tube sizes at initial pressures higher than 0.2 bar for the propane-oxygen mixture and higher than 0.8 bar for the diluted mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Панацеей при решении всех этих задач может служить применение камер сгорания с детонационным горением, исследования которых ведутся во всем мире [7]. Активно изучаются различ-ные способы интенсификации горения, в том числе и перехода медленного горения в детонацию [8], а также инициирования детонации при помощи СВЧ-разряда [9]. Пока детонационные технологии не соз-даны, актуальна разработка экономичных методов интенсификации обычного медленного горения.…”
Section: On the Possibility Of Burning Acceleration In The Combustionunclassified
“…Панацеей при решении всех этих задач может служить применение камер сгорания с детонационным горением, исследования которых ведутся во всем мире [7]. Активно изучаются различ-ные способы интенсификации горения, в том числе и перехода медленного горения в детонацию [8], а также инициирования детонации при помощи СВЧ-разряда [9]. Пока детонационные технологии не соз-даны, актуальна разработка экономичных методов интенсификации обычного медленного горения.…”
Section: On the Possibility Of Burning Acceleration In The Combustionunclassified
“…An experimental demonstration of a longitudinal, high-voltage, nanosecond, gas-discharge application for initiation of detonation was proposed by Starikovskii [37] and performed by Starikovskiy and co-workers [21,[54][55][56][57][58][59][60][61].…”
Section: (C) Deflagration-to-detonation Transition By Longitudinal Plasma Filamentsmentioning
confidence: 99%
“…However, the DDT time was significantly longer and amounted to 150 ms. At the same time, ICCD imaging showed that the ignition did not occur simultaneously over the channel. Instead, a flame was seen originating in the region closest to the high-voltage electrode after a delay of over 50 ms An experimental study of detonation initiation by high-voltage, nanosecond gas discharge has been performed in a smooth detonation tube with a four-channel discharge chamber designed to enable a gradient initiation mechanism [59,60]. Stoichiometric propane-oxygen mixtures diluted by nitrogen were used at initial pressures from 0.2 to 1 bar.…”
Section: Deflagration-to-detonation Transition Initiation By Streamer Discharge: Gradient Mechanismmentioning
confidence: 99%